REVITALISASI PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL MELALUI KEGIATAN KEAGAMAAN DI MA ARRIYADLAH - Zubaidi, Ahmad; Adelia Putri Azizah (LPPM STAI Muhammadiyah Probolinggo, 2026)
Character education in madrasahs plays a strategic role in shaping students who are religious, disciplined, and responsible. However, habituation programs in schools are often not optimally integrated with the local religious wisdom of the community. MA Arriyadlah Pandean has consistently developed istighosah and congregational dhuha prayer activities as forms of religious habituation rooted in local traditions. This study aims to analyze the revitalization of istighosah and congregational dhuha prayer as a model of character education based on local wisdom at MA Arriyadlah Pandean. The research employed a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with the head of the madrasah and Aqidah Akhlak teachers, and documentation of religious activities. Data analysis was conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that istighosah strengthens religious values, spirituality, and togetherness, while congregational dhuha prayer fosters discipline, responsibility, and empathy among students. These activities integrate Islamic values and local wisdom harmoniously, creating a religious and humanistic school culture. The revitalization of these religious practices effectively supports religio-cultural–based character education and offers a contextual model that can be adopted by other madrasahs.